2021
DOI: 10.1146/annurev-immunol-101819-025146
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Regulation of T Helper Cells

Abstract: As the professional antigen-presenting cells of the immune system, dendritic cells (DCs) sense the microenvironment and shape the ensuing adaptive immune response. DCs can induce both immune activation and immune tolerance according to the peripheral cues. Recent work has established that DCs comprise of several phenotypically and functionally heterogeneous subsets that differentially regulate T lymphocyte differentiation. This review summarizes both mouse and human DC subset phenotypes, development, diversifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
169
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(172 citation statements)
references
References 291 publications
1
169
0
2
Order By: Relevance
“…This model allows us to dissect the specific receptors and pathways required for the generation of detrimental alloimmunity during transfusion. Storing HOD RBCs for transfusion allows for examination of the innate and adaptive immune response to a model human RBC antigen after transfusion of RBCs stored under conditions that are used in hospitals globally (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)21). HOD RBCs processed and stored for 12 days at 4°C induced a robust anti-HOD alloantibody response post transfusion into wild type (WT) C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This model allows us to dissect the specific receptors and pathways required for the generation of detrimental alloimmunity during transfusion. Storing HOD RBCs for transfusion allows for examination of the innate and adaptive immune response to a model human RBC antigen after transfusion of RBCs stored under conditions that are used in hospitals globally (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)21). HOD RBCs processed and stored for 12 days at 4°C induced a robust anti-HOD alloantibody response post transfusion into wild type (WT) C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…In order to mount an adaptive immune response, specifically naïve T and B cell priming, first the innate immune system must be activated. This involves activation of antigen-presenting cells, such as dendritic cells (DCs), through innate immune receptors termed pattern recognition receptors (PRRs); this is a crucial checkpoint in regulating T cell-dependent B cell antibody responses (20). Indeed, our previous work demonstrated that although transfused RBCs are consumed by and activate numerous antigen presenting cells in the spleen, only type 2 conventional dendritic cells (cDC2s) were required for alloantibodies (21), likely due to a defect in T cell priming (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 T cell compartments can be broadly organized across three major classes of immune response. Divergent lineage defining protein and transcriptional signatures assort with type 1 inflammatory (targeting intracellular microbes), type 2 anti-inflammatory (targeting extracellular microbes), and type 3 mucosal (protecting barrier surfaces) immune response modules 24,25,26,27 .…”
Section: Highlightsmentioning
confidence: 99%
“…The microbe-tailored is the most prevalent and widely accepted model (Iwasaki and Medzhitov, 2015). It is an 'umbrella' term under which several sub-models are interchangeably used to explain how different pathogen-associated molecular patterns (PAMPs) activate various types of dendritic cells or other accessory cells to create different cytokine milieu that in turn drive different types of Th programs (Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%